2020
DOI: 10.1021/acs.jpcb.9b11005
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol Reduces Partitioning of Antifungal Drug Itraconazole into Lipid Bilayers

Abstract: Cholesterol plays a crucial role in modulating the physicochemical properties of biomembranes, both increasing mechanical strength and decreasing permeability. Cholesterol is also a common component of vesicle-based delivery systems, including liposome-based drug delivery systems (LDSs). However, its effect on the partitioning of drug molecules to lipid membranes is very poorly recognized. Herein, we performed a combined experimental/computational study of the potential for the use of the LDS formulation for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 54 publications
(89 reference statements)
4
18
0
Order By: Relevance
“…MD simulations showed that this is not the right choice because cholesterol and itraconazole do not mix well and separate into small domains (Poojari et al, 2020). This observation was next validated in experimental studies, which showed decreased affinity of itraconazole toward liposomes containing cholesterol (Poojari et al, 2020). The observed behavior of the itraconazole may be explained by its structure: it is a long rigid molecule with a few weakly polar groups distributed along the molecule backbone.…”
Section: Drug Loading and Controlled Releasementioning
confidence: 91%
See 1 more Smart Citation
“…MD simulations showed that this is not the right choice because cholesterol and itraconazole do not mix well and separate into small domains (Poojari et al, 2020). This observation was next validated in experimental studies, which showed decreased affinity of itraconazole toward liposomes containing cholesterol (Poojari et al, 2020). The observed behavior of the itraconazole may be explained by its structure: it is a long rigid molecule with a few weakly polar groups distributed along the molecule backbone.…”
Section: Drug Loading and Controlled Releasementioning
confidence: 91%
“…Thus, the incorporation of cholesterol into the liposome-itraconazole formulation was the next step. MD simulations showed that this is not the right choice because cholesterol and itraconazole do not mix well and separate into small domains (Poojari et al, 2020). This observation was next validated in experimental studies, which showed decreased affinity of itraconazole toward liposomes containing cholesterol (Poojari et al, 2020).…”
Section: Drug Loading and Controlled Releasementioning
confidence: 93%
“…Multilayer lipid membranes are essential to life, perform many essential functions in biology, and regulate many cellular processes 1 . Multilayered lipid membranes have a variety of functional advantages over single-lipid membranes, such as to organize processes spatially, significantly increase membrane protein concentration because of an increase in surface area, and compartmentalize molecules 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Chol also can play the same position in vesicle-based delivery systems, including liposome-based drug delivery systems. However, its position in the partitioning of drug molecules to lipid membranes is poorly identified 1 . In general, Chol can modify the physical properties of a lipid membrane.…”
Section: Introductionmentioning
confidence: 99%
“…Understanding the mechanism of translocation and binding of a variety of drugs, transfection reagents, and antifungal/ antimicrobial compounds also remains a hot topic, 17,18 with additional complexity arising from the presence of certain lipids, 19 synergetic effects, 20 and modulation of pH. 21,22 Apart from these more applied studies, this Virtual Special Issue includes exciting contributions aimed at increasing our understanding of fundamental physical mechanisms that govern membrane behavior.…”
mentioning
confidence: 99%